Determination of Purchase Intention Applying Technology Acceptance Model: A Case of Facebook Influence - Mishra, Udgam (Dristikon: A Multidisciplinary Journal, 2020)
The paper aims to determine the influence of Face book on purchase intention applying Technological acceptance model. The data are obtained from self-administered questionnaire of Facebook users of Biratnagar. The response received has been analyzed by several statistical tools namely Frequency Distribution, Cronbach‘s Alpha Reliability test, Pearson Correlation Coefficient and Linear Regression Analysis, computed by Software Package for Social Science(SPSS) version 26. The main conclusion drawn from this study states that perceived usefulness and perceived ease to use have significant relationship with purchase intention. The findings reveal that perceived usefulness has more influence on purchase intention than ease to use. This study recommends that Marketers should give more focus on branding the Face book page and maintain immediate connection with Face book users.